2016
DOI: 10.1007/s12325-016-0430-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Short-term Deterioration in Maintenance-naïve Patients with COPD Receiving Umeclidinium/Vilanterol and Tiotropium: A Pooled Analysis of Three Randomized Trials

Abstract: IntroductionDual bronchodilator therapy is reserved as a second-line treatment in patients with chronic obstructive pulmonary disease (COPD) and provides benefits in lung function and health status versus monotherapy. The aim of this study was to determine whether early initiation of a dual bronchodilator versus monotherapy reduced the risk of deterioration in COPD.MethodsThis post hoc pooled analysis investigated the efficacy and safety of umeclidinium/vilanterol (UMEC/VI) 62.5/25 mcg/day compared with tiotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
87
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(99 citation statements)
references
References 18 publications
10
87
0
2
Order By: Relevance
“…Importantly, the treatment difference between the LAMA/LABA combinations observed in this study was greater in magnitude than that reported with TIO/OLO versus TIO alone in a similar MN population in the replicate OTEMTO studies [17]. Using dual therapy as a first-line maintenance therapy has been shown to provide the opportunity for improved bronchodilation and therefore potential for optimal symptom management and greater protection against further disease deterioration [16][17][18]. The greater lung function improvements with UMEC/VI over TIO/OLO in this MN population suggest that there is no ceiling to bronchodilation potential in patients with moderate COPD.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Importantly, the treatment difference between the LAMA/LABA combinations observed in this study was greater in magnitude than that reported with TIO/OLO versus TIO alone in a similar MN population in the replicate OTEMTO studies [17]. Using dual therapy as a first-line maintenance therapy has been shown to provide the opportunity for improved bronchodilation and therefore potential for optimal symptom management and greater protection against further disease deterioration [16][17][18]. The greater lung function improvements with UMEC/VI over TIO/OLO in this MN population suggest that there is no ceiling to bronchodilation potential in patients with moderate COPD.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, demonstration of a statistically significant treatment difference on supplemental rescue medication use, a clinical endpoint reflecting an effect on symptoms [36], shows that the potential for better symptom control with improved bronchodilation in MN patients is also a realistic goal. Currently, data on the impact of initiating maintenance therapy with dual bronchodilators in MN patients are sparse and are largely obtained using post hoc analysis of prospectively collected data [16,17,24]. These analyses consistently indicate no diminished patient benefit or safety concern when opting to use dual therapy as a first-line treatment option.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with LABA/LAMA is recommended based on its superior results versus standard of care therapy with LAMA monotherapy or LABA/inhaled corticosteroid (ICS), and lower risk of development of pneumonia versus ICS‐containing treatment . Dual bronchodilator therapy with fixed‐dose LABA/LAMA has demonstrated improvements in lung function and health‐related quality of life, and has reduced the usage of rescue medication in patients with prior maintenance therapy with a single bronchodilator …”
Section: Introductionmentioning
confidence: 99%